EFEK EKSTRAK ETHANOL DAUN MIMBA TERHADAP GONADOSOMATIC INDEX (GSI), JUMLAH DAN UKURAN FOLIKEL ATRESIA PADA MENCIT (Mus musculus L.) BETINA - Nurul Hidayah; Agung Janika Sitasiwi; Siti Muflichatun Mardiati (Jurnal Pro-Life, 2018)
Neem leaves contain flavonoid, triterpenoid and saponin compounds that have antifertility potential to suppress of reproduction rate of rodentia pests. The purpose of this study was to examine the effect of neem leaf ethanol extract on gonadosomatic index (GSI), number and size of atresia follicles in female mice. This study used a Completely Randomized Design Method consist of 5 treatments and 4 replications namely K + (Contraceptive Pills); K- (Aqua); P1, P2 and P3 (Treatment of neem leaf ethanol extract at dosage of 8.4 mg / kgBW, 11.2 mg / kgBW and 14 mg / kgBW). The treatment was administered orally at a volume of 0.2 ml / animal every morning for 21 days. Measurement of body weight was conducted at the beginning of treatment and every 7 days. The ovaries were isolated, weighed and histologically processed using paraffin method and H & E staining. the number and diameter of atresia follicles were counted on ovaries. The data was analyzed using ANOVA test and DMRT test at 95% confidence level. The results showed that neem leaf ethanol extract had no significant effect GSI and diameter of atresia follicle but had significant effect on the number of atresia follicle. It can be concluded that neem leaf ethanol extract can increase the number of atresia follicle in mice by suppressing the synthesis and action of reproductive hormone. Keywords: mimba leaf, atresia follicle, GSI, mice